2022
DOI: 10.5098/hmt.18.44
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Thin Layer Drying of Ganoderma Lucidum by Radio Frequency Assisted Heat Pump Drying

Abstract: This study determined the most appropriate thin layer drying model, the effective moisture diffusivity and the activation energy of moisture within Ganoderma lucidum in radio frequency (RF) assisted heat pump drying method. The thin layer drying experiments were conducted with input drying parameters such as: drying temperature of 40, 45 and 50°C and RF power of 0.65, 1.3 and 1.95 kW. In order to select a suitable form of drying curve, seven different thin layer drying models (Lewis, Page, Modified Page, Hende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Xu Zhou and Shaojin Wang (2019) studied the drying techniques using RF for drying agricultural products and foods, in which, the RF volumetric heating mechanism significantly improved the drying rate and the quality of the dried products. Le Anh Duc et al, (2022) conducted the RF assisted heat pump drying of Ganoderma lucidum and the experimental drying results showed that increasing RF power increased the moisture ratio and reduced the drying time significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Xu Zhou and Shaojin Wang (2019) studied the drying techniques using RF for drying agricultural products and foods, in which, the RF volumetric heating mechanism significantly improved the drying rate and the quality of the dried products. Le Anh Duc et al, (2022) conducted the RF assisted heat pump drying of Ganoderma lucidum and the experimental drying results showed that increasing RF power increased the moisture ratio and reduced the drying time significantly.…”
Section: Introductionmentioning
confidence: 99%